2020
DOI: 10.1016/j.gca.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Water and heat: New constraints on the evolution of the CV chondrite parent body

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 70 publications
10
49
0
Order By: Relevance
“…The peak metamorphic temperatures of the considered CV3 oxB are calculated to be between 220 -C, however PMTs for CV3 oxA vary from C to ~636 C, indicating that studied CV3 oxB chondrites are less metamorphosed (thus more primitive) than CV3 oxA chondrites. This is in agreement with the literature (e.g., Bonal et al 2020). Furthermore, our data show a large temperature increase (150 °C) between the CO3.2 and CO3.4 petrologic types, but much less difference between CO3.4 and CO3.6 (20 C), as shown in Figure 11.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The peak metamorphic temperatures of the considered CV3 oxB are calculated to be between 220 -C, however PMTs for CV3 oxA vary from C to ~636 C, indicating that studied CV3 oxB chondrites are less metamorphosed (thus more primitive) than CV3 oxA chondrites. This is in agreement with the literature (e.g., Bonal et al 2020). Furthermore, our data show a large temperature increase (150 °C) between the CO3.2 and CO3.4 petrologic types, but much less difference between CO3.4 and CO3.6 (20 C), as shown in Figure 11.…”
Section: Resultssupporting
confidence: 93%
“…Bonal et al (2020) reported that the CV3 oxA chondrites contain higher abundance of metal and lower Ni in sulfides, while they have similar abundance of matrix. The CV3 red chondrites present signatures of either aqueous alteration or metasomatism(Krot et al, 1995, Huss et al 2006, they contain less matrix, more metal and Ni-poor sulfides relative to the oxidized CV3 chondrites(Bonal et al 2020).…”
mentioning
confidence: 99%
“…Within this array the CM chondrites appear to define a line offset from that defined by CV, CO and CR chondrites, which can be explained by different shapes of the 3-µm band. The CM chondrite (as well as the CR1 GRO 95577) have a band with a maximum of absorption around 2.7-2.80 µm while CO, CV and CR tend to have an absorption maxima in the 2.85-3.0 µm range (Eschrig et al, 2020). Figure 3 presents the relation between carbonaceous chondrites water content and the band depth at 2.9 µm.…”
Section: Calibration Curvementioning
confidence: 99%
“…Here, the approach is in essence similar to Rivkin et al (2003) but we build on significant progress in these issues. First, reflectance of chondrite meteorites under asteroidal conditions have been obtained for about 40 samples (Potin et al, 2020b;Eschrig et al, 2020), and the effects of observation geometry on the 3-µm band have been recently quantified (Potin et al, 2019). Second, recently published space-based observations by the Akari telescope offer a full description of the 3-µm feature for several tens of Main-belt asteroids.…”
Section: Introductionmentioning
confidence: 99%
“…The following references were used to support the classification of meteorites in MB109: Bonal et al. (2020); DeHart et al. (1992); Evans et al.…”
Section: Trends and Specificitiesmentioning
confidence: 99%